A study of the factors influencing the life cycle of synthetic anion exchange resins, with special reference to the extraction of uranium - Robinson, R. E. (My University, 1953)
Investigations have been carried out into the life of various Anion Exchange Resins employed on the Rand for the extraction of uranium from the uranium Leach Liquors. It was found that in the case of the leach liquors produced at the western Reefs pilot plant and at the West Rand Consolidated Uranium plant, the major factor causing a decrease in the efficiency of the Ion exchange resins was the presence of certain chemical poisons in these pregnant solutions. [No abstract provided. Information taken from General Summary]
A Thesis presented in the University of the Witwatersrand, Johannesburg for the degree of Doctor of Philosophy, 1953
Keywords: Uranium--Metallurgy; Ion exchange resins; Cyanide process